A Service-Oriented Architecture with Data Virtualization Support for Cloud-Based Wireless Sensor Networks - Reyes, Ronald Jared Romero; Mendonça, Francisco Ferreira de; Dias, Kelvin Lopes (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Current solutions for sensor-cloud integration do not offer tools or platforms providing both efficient data management and standardized interfaces for the development of WSN-based applications on a shared infrastructure. This paper proposes a new architecture based on the paradigm of Service-Oriented Computing and virtualization of sensors for efficient management of heterogeneous WSNs data. The implementation and analysis were carried out on a testbed based on the OpenStack platform. Results showed that the architectural components incur minimal impact on system performance.